Community Forest: March Towards Secondary Phase - Adhikari, Manoj (KMC Research Journal, 2018)
Nepal has been fighting a battle against deforestation and enables to restore major of its forest. Forest conservation is possible through the practice of the concept of community forestry. However conserved forest is only able to supply basic amenities to users. The vast timbered and non timbered forest products, which could be the major source for income has been shadowed. This study was conducted to assess, and understand the problems and prospectus of secondary development of community forest among users’ group management committee members and to understand problems and prospects of secondary development of community forest. The study was done using both the research methods i.e. primary and secondary data collection. The major finding of the study shows that user groups have knowledge about secondary development of community forest .Major problems for secondary development of community forest are lack of research and development in forestry, along with the lack of resources with users’ groups. The prospects for secondary development of community forest are that they have been endowed with both timbered and not timbered forest products.